THE EFFECT OF ORGANIZATIONAL JUSTICE, JOB SATISFACTION, AND ORGANIZATIONAL COMMITMENT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) OF THE PRINCIPLES - Musringudin Musringudin; Makruf Akbar; Netti Karnati (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
The objective of this research is to measure the effect degree of organizational justice, job satisfaction, and organizational commitment on organizational citizenship behavior of the principles of public high school in Jakarta. The research was done from November to December  2016. The data were collected from the principles that selected as a respondent, through the questionnaires. This research consist of 90 principles as asample of 116 of the total population around Jakarta province. The amount of 90 samples decided based on the proportional random sampling technique. Then, the data calculated using path analysis.The result of the study shows: 1) there is a positive effect of organizational justice variable on organizational citizenship behavior (OCB). The data analysis said the path coefficient value of organizational justice on OCB (p41) was 0,221.  2) the positive effect of job satisfaction on OCB also able to be seen from the value of path coefficient (p42) in the amount of 0,205. 3) organizational commitment as shown in the path coefficient amount (p43) was 0,212, it  indicated a positive effect on OCB. 4) the effect of organizational justice on organizational commitment described a positive contribution. The amount of path coefficient (p31) was 0,253. 5) the effect of job satisfaction on organizational commitment (p32) as big as 0,237 of path coefficient. 6) organizational justice variable indicated a positive influenced on job satisfaction (p21), with the amount of path coefficient 0,286. Finally, it is recommended for public educational institution to boost the whole components in education field to do the best for it organization. Especially for the principles must behave that showed helpful, Altruism, Conscientiousness, Sportsmanship, Courtesy and Civic VirtueKeywords: work ethic, team chracteristics, organizational justice, and, job performance